Pengaruh E-Filing dan E-Billing Terhadap Kepatuhan Wajib Pajak dalam Pelaporan dan Pembayaran Pajak (Studi Kasus di KPP Pratama Malang Utara) - Larasati Puspaharisti; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The objectives of this study are: 1) To find out the effect of e-filling on the compliance of Taxpayers in reporting Annual Tax Returns influential or not at KPP Pratama Malang Utara, 2) To find out the effect of e-billing on Taxpayer compliance in payment influential or not at KPP Pratama Malang Utara. By using an associative quantitative approach, the results showed that simultaneously e-Filing had a positive and significant effect on Taxpayer Compliance in Tax Payments, simultaneously e-Billing had a positive and significant effect on Taxpayer Compliance in Tax Payments, partially e-Filing has a positive and significant effect on Taxpayer Compliance in Tax Reporting, and partially e-Billing has a positive and significant effect on Taxpayer Compliance in Tax Payments.Keywords: e-filing, e-billing, Tax Compliance, Tax Reporting, Tax Payment.